2004
DOI: 10.1037/0022-3514.86.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence: Is It the Epidemiologists' Elusive "Fundamental Cause" of Social Class Inequalities in Health?

Abstract: Virtually all indicators of physical health and mental competence favor persons of higher socioeconomic status (SES). Conventional theories in the social sciences assume that the material disadvantages of lower SES are primarily responsible for these inequalities, either directly or by inducing psychosocial harm. These theories cannot explain, however, why the relation between SES and health outcomes (knowledge, behavior, morbidity, and mortality) is not only remarkably general across time, place, disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
405
2
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(432 citation statements)
references
References 117 publications
14
405
2
11
Order By: Relevance
“…That is, cognitive tests (of Memory and Speed) were a predictor of less subsequent change in brain volume. It is possible that this is due to the established relations of cognitive ability with health behaviors: for instance, individuals with better cognitive ability tend to smoke less and exercise more (Gottfredson, 2004), and these lifestyle factors may impact brain structure (e.g. [Almeida et al, 2011; Hillman et al, 2008]; note that such factors were not measured in this study).…”
Section: Discussionmentioning
confidence: 98%
“…That is, cognitive tests (of Memory and Speed) were a predictor of less subsequent change in brain volume. It is possible that this is due to the established relations of cognitive ability with health behaviors: for instance, individuals with better cognitive ability tend to smoke less and exercise more (Gottfredson, 2004), and these lifestyle factors may impact brain structure (e.g. [Almeida et al, 2011; Hillman et al, 2008]; note that such factors were not measured in this study).…”
Section: Discussionmentioning
confidence: 98%
“…Since the time of Spearman, many researchers have posited that cognition is comprised of a general intelligence (g factor) that serves as a foundation for specific strengths and weaknesses in areas such as memory and attention. Gottfredson (2004) presents evidence that g is a strong predictor of health outcomes, including cigarette, alcohol and substance use, as well as accidents related to use.…”
Section: Discussionmentioning
confidence: 99%
“…Since the time of Spearman, many researchers have posited that cognition is comprised of a general intelligence (g factor) that serves as a foundation for specific strengths and weaknesses in areas such as memory and attention. Gottfredson (2004) presents evidence that g is a strong predictor of health outcomes, including cigarette, alcohol and substance use, as well as accidents related to use.Although categorical systems such as DSM-IV tend to emphasize differences among disorders, dimensional approaches to psychopathology have suggested that one or more general psychopathology factors may exist (Helzer, et al, 2006). A good example is the Child Behavior Checklist (CBCL), which includes broadband internalizing and externalizing scales as well as narrower clinical scales assessing specific components of psychopathology.…”
mentioning
confidence: 99%
“…From the perspective of Millet & Dewitte's hypothesis referenced above, particularly important is the relationship between intelligence and access to resources. Studies have demonstrated that as a predictor of socioeconomic status intelligence is more accurate than the status of parents (Gottfredson, 2004). Whether measured in childhood or adulthood, intelligence is predictive for the social status of occupation and income (correlation of 0.51 and 0.31, respectively) (Judge, Higgins, Thoresen & Barrick, 1999).…”
Section: Introductionmentioning
confidence: 99%